Eksplorasi Konsep Etnomatematika pada Gerakan Tarian Topeng Ireng - 'Ulya, Khomisa Anisatul (Pusat Studi Pengembangan Pembelajaran Matematika, 2023)
Mask ireng dance is a form of cultural heritage that originally developed in the Magelang area, Central Java. That said, this mask ireng dance depicts a group of dashing soldiers who were camouflaged in fighting the Dutch colonization at that time. The purpose of this study is to explore the relationship between mathematics and culture, particularly in the traditional dance Topeng Ireng. This research uses an ethnograpic approach, which is an empirical and theoretical approach to obtain a comprehensive description and analysis of a culture based on field notes obtained from the collection of information. The results of this study indicate that in traditional Mask ireng dances have various geometry concepts, such as vertical lines, horizontal lines, intersecting lines, acute angles, and obtuse angles. Therefore, this traditional dance can be used as a starting point or context for curriculum development for elementary and secondary school students. In addition, it can change the students’ paradigm that math can be related to daily activities and culture and can be learned in a fun way.